Resurgence of canine parvovirus 2a strain in the domestic dog population from Argentina - Gallo Calderon, Marina Beatriz (2015)
Ninety-three rectal swab samples were taken, from dogs suspected of canine parvovirus (CPV) infectionand analyzed by PCR. A fragment of the VP2 gene, was amplified in 41 (44%) of them, resulting CPVpositive samples. Sequencing analysis of these PCR products showed that 37 samples (90.2%) belongedto the CPV2c type, whereas four samples (9.8%) were identified as CPV2a, which has not been found since2008.It was also found that 24 out of 37 CPV2c samples (65%), carried the mutation Thr440Ala, whereas thismutation was absent in the four CPV2a strains reported herein.Using phylogenetic analysis of the full length VP2 gene, which was amplified by PCR in six local samples,it was seen that CPV2a Argentine strains reported in this study, were genetically closer to a previouslocal CPV2a isolate (year 2003) and to a South African CPV2a strain, than to any of the recently reportedUruguayan CPV2a strains.The results obtained in this work, together with those reported previously in Uruguay strongly suggestthat, in spite of the geographical proximity, wild type CPV strains undergo different evolutive pathwaysin each country, resulting in the prevalence of different strains in related dog populations.Further extensive epidemiological studies are needed in order to improve the understanding of CPVevolution.